2017
DOI: 10.1038/labinvest.2017.2
|View full text |Cite
|
Sign up to set email alerts
|

APX-115, a first-in-class pan-NADPH oxidase (Nox) inhibitor, protects db/db mice from renal injury

Abstract: Recent studies have suggested that renal Nox is important in the progression of diabetic nephropathy. Therefore, we investigated the effect of a novel pan-NOX-inhibitor, APX-115, on diabetic nephropathy in type 2 diabetic mice. Eight- week-old db/m and db/db mice were treated with APX-115 for 12 weeks. APX-115 was administered by oral gavage at a dose of 60 mg/kg per day. To compare the effects of APX-115 with a dual Nox1/Nox4 inhibitor, db/db mice were treated with GKT137831 according to the same protocol. AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 48 publications
(64 reference statements)
1
54
0
Order By: Relevance
“…Our previous studies completed in both type 1 and 2 diabetic mice demonstrated that APX-115 has a comparative renoprotective effect to losartan (a mainstay treatment in DKD) and GKT137831 (a dual Nox inhibitor) respectively [17,18]. Particularly, the present study provides additional confirmatory evidence in another murine model and shows the dose-dependent effect of APX-115 in diabetic kidney injury.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Our previous studies completed in both type 1 and 2 diabetic mice demonstrated that APX-115 has a comparative renoprotective effect to losartan (a mainstay treatment in DKD) and GKT137831 (a dual Nox inhibitor) respectively [17,18]. Particularly, the present study provides additional confirmatory evidence in another murine model and shows the dose-dependent effect of APX-115 in diabetic kidney injury.…”
Section: Discussionsupporting
confidence: 74%
“…Unlike the GKT compounds, APX-115 is a pan-Nox inhibitor. Our study in type 2 diabetic kidney injury with db/db mice suggested that APX-115 was more effective than GKT compound in decreasing plasma isoprostanes (a lipid peroxidation and oxidative stress marker), serum creatinine, urinary albumin excretion, as well as mesangial expansion [17]. Nox 1 and 2 are the major sources of ROS in the artery wall in condition such as hypertension, hypercholesterolemia, as well as aging [25].…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…In db/db and db/m diabetic mice, treatment with APX-115, a novel pan-NOX-inhibitor, or GKT, enhanced lipid profile, attenuated insulin resistance, and reduced F4/80-positive cells, a marker of macrophage infiltration in fat tissue. Furthermore, there was a significant decrease in mRNA expression of inflammatory chemokines such as Plasminogen activator inhibitor-1 (PAI-1) and MCP-1 upon NOX inhibition [137].…”
Section: The Cross-link Between Nadph Oxidases-induced Oxidative Strementioning
confidence: 99%